2011
DOI: 10.1136/jmg.2010.088096
|View full text |Cite
|
Sign up to set email alerts
|

Screening patients referred to a metabolic clinic for lysosomal storage disorders

Abstract: This study demonstrates the sensitivity and specificity of this technology to accurately identify 99% of LSD patients, with the exception of one MPS II false negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…Indeed, in ML II or III, the mannose-6-phosphate tag on the lysosomal enzymeswhich ensures sorting to the lysosome -is missing, leading to the excretion of the enzymes into the plasma. This yields elevated in vitro plasma enzyme activities, which can also be found in DBS (Gusina and Tsukerman 1988;Fuller et al 2011;Wood et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in ML II or III, the mannose-6-phosphate tag on the lysosomal enzymeswhich ensures sorting to the lysosome -is missing, leading to the excretion of the enzymes into the plasma. This yields elevated in vitro plasma enzyme activities, which can also be found in DBS (Gusina and Tsukerman 1988;Fuller et al 2011;Wood et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of using DBS for enzymatic diagnosis of MPS and ML II/III has been demonstrated (Chamoles et al 2001b;Chamoles et al 2001a). In the past years, fluorometric methods, immunocapture enzyme assays and even high-throughput tandem mass spectrometry assays have been developed and optimised to allow (large-scale) screening for LSDs (Blanchard et al 2008;Dean et al 2006;Duffey et al 2010a;Duffey et al 2010b;Fuller et al 2011;Reuser et al 2011;Wang et al 2007;Wolfe et al 2011). However, all studies using DBS were feasibility studies, including only patients with a confirmed diagnosis of MPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early diagnosis will thus be essential and can only be achieved by increasing awareness for MPS III and, probably best, by NBS. Earlier studies showed that NBS for MPS IIIA is feasible, for example, by measuring HS concentrations or lysosomal protein concentrations in dried blood spots 22, 31, 32. Early diagnosis, especially through NBS, will make reliable assessment of the phenotype crucial, either by genotyping or, if that is inconclusive, by other methods such as the method reported here.…”
Section: Discussionmentioning
confidence: 87%
“…The availability of the multiplex technology has facilitated the technical aspect of testing, making it easier to identify LSDs. Pilot studies of newborn screening for specific LSDs (Fabry, Pompe, Gaucher and MPS-I) carried out so far in some countries have indicated a much greater prevalence than the prevalence estimated by clinical diagnosis (18,19). This increase in prevalence is primarily due to recognition of later-onset forms of LSDs.…”
Section: Diagnostic Strategy For Lsdsimperative For Early Detectionmentioning
confidence: 99%